Аксиологический аспект лексической системы - Гудавичюс, Алоизас (Slavistica Vilnensis, 1998)
Axiological systems of languages are of great interest for ethnolinguistics. The evaluation of reality in a language is a specific characteristic of its semantics, reflecting a certain nation’s subjective world outlook, fixed in its language. In language axiology the two aspects should be singled out: a) the aspect of logical evaluation, i.e. nomination of things and phenomena according to either a positive or negative aspect, which reflects world outlook of a given language, b) the aspect of emotional evaluation, reflecting a subjective point of view, which creates the emotional attitude of certain language. Traditionally, the emotionality of Russian and other Slavic languages is, first of all, associated with their ample derivational opportunities to express emotional evaluation. However, other spheres, such as lexical expression of positive/negative emotions and evaluation, metaphorization, and associative links between words, determining their cognitive value in the speaker’s consciousness, are also important for language axiology. The abundance of words to express negative emotions (the semantic field of sadness) in Russian can be given as an example. This language is also characterized by a negative description of people by means of zoomorphisms, while bionims, i.e. names of plants, usually have positive associations. The description and comparison of these axiological characteristics in different Slavic languages would be a serious basis for research into the peculiarities of Slavic culture and mentality. The paper presents as an example of such axiological investigation the analysis of semantic field of speech in the Russian language.